Interactive Effects of Warming and Nitrogen Availability on Soil Carbon Fluxes: Implications for a Changing Climate - Waldron, Emma (My University, 2024)
The excess of greenhouse gasses like carbon dioxide in the atmosphere urgently calls for a deeper understanding of existing natural mechanisms for carbon sequestration. Soils act as a critical natural carbon sink, storing at least twice as much carbon as there is globally in the atmosphere and in plant biomass combined. However, climate change and associated increases in average temperatures can impact soil carbon storage processes, converting carbon sinks to carbon sources. The response of soil carbon to warming is complex and depends on many environmental factors. This study focuses on nitrogen (N) availability, which may mediate the effects of warming on soil carbon via its influence on microbial activity and decomposition. Strong support for this hypothesis is lacking, however, as these variables are difficult to isolate in the field. In this greenhouse experiment, I cross two warming treatments with four N treatments in order to disentangle some of these relationships. To get a picture of how carbon fluxes responded to my treatments, I measured soil organic matter (SOM) as a proxy for the amount of carbon stored in the soil, and soil respiration rate to see how much carbon the soil was releasing. I also measured nitrate and ammonium levels as well as nitrification and mineralization rates in the soil to get a fuller understanding of how my treatments actually affected both N availability and the soil microbial activity governing N availability. I found significant effects from both my warming treatments and my nitrogen treatments, along with significant interactions between the two. Because my pots had living microbes and plants, there were feedbacks between N and C above and belowground, creating complicated relationships between warming, N, SOM, and soil respiration (as expected). Further clarification of these dynamics will be critical for making accurate climate predictions and for strategically targeting restoration efforts to mitigate climate change.
Keywords: climate change; soil carbon fluxes; nitrogen availability; global warming